(untitled) (European Journal of Pure and Applied Mathematics, 2017)
Theory of approximation is a very extensive field and study of approximation via qcalculus and (p, q)- calculus is of great mathematical interest with great practical importance. Positive approximation processes play an important role in approximation theory and appear in a very natural way dealing with approximation of continuous functions, especially one, which requires further qualitative properties such as monotonicity, convexity and shape preservation and so on. This paper deals with the q- form of Dunkl generalization of SzÂ´asz - Beta type operators. Estimation of their moments and establishing basic approximation results which comprise weighted approximation and direct estimates in view of modulus of continuity is the aim of this paper.